Quality of Ethics Education in Producing Ethical Future Accountants: A Conceptual Paper - Shahida Shaharuddin; Nurul Nazlia Jamil; Suhaila Abdul Hamid (Human Resource Academic Research Society, 2024)
Vol. 12, No. 3, 2022, Page (116 - 131)